JORDANIAN AND SAUDI STAND TOWARD BAGHDAD ALLIANCE - Al-Ammary, Tariq Turki; Al-Rousan, Mohammad Ali; Al-Azzam, Tarik Mohammad (European Scientific Journal, ESJ, 2012)
This study aimed at understanding, analyzing and explaining the stand of both Jordan and Saudi Arabia towards Baghdad Alliance. The research revealed the fact that Baghdad Alliance, under the control of Britain, divided the Arabs into supporters and opposers of it. Iraq was one of the first countries to join it and encouraged others to do the same, especially Jordan, the fact which put Jordan in the middle of conflict. An opposing Arab front was formed which consisted of Egypt and Saudi Arabia. The first considered it as a threat to its leading position in the Arab World, while the other considered it as a point of strength to its enemies in Iraq and Jordan. Therefore, they both sought to oppose the alliance by sharing roles. Egypt took the informational role to influence the Arabs’ public opinion, while Saudi Arabia took the funding role to establish opposing popular and political fronts, the fact which led to its failure, paving the way for the United States to take Britain’s place through Eisenhower’s Project.